Identification of Herbal Compounds as Thymidylate Synthase Inhibitors that more Potent than 5-Fluorouracil using Molecular Docking - Pratama, Yoga Mulia; Indarto, Dono; Suselo, Yuliana Heri (Nexus Kedokteran Translasional, 2015)
Background: Development of new selective anticancer drug is an important necessary. Because of that, some effective way to screen herbal compounds which have good potency for developing drug is needed, one of them is using molecular docking methods. In this study, researchers identify herbal compounds as new thymidylate synthase (TS) inhibitors which more potent than 5-Fluorouracil (5-FU) using molecular docking. Methods: Three-dimensional structure samples of herbal compounds from Indonesian herbal database (herbaldb.ui.ac.id) were docked with three-dimensional structure of TS protein using iGEMDOCK program. Then, the compounds which have lower docking score than fdUMP, as standard ligand, clustered using ChemMine. Results: The docking result showed that 27 herbal compounds have docking score lower than fdUMP in iGEMDOCK program. The 27 compounds have higher affinity to fdUMP and it can form a stable complex with TS protein. Protein-ligand complexes showed that all of 27 compounds have same binding site with fdUMP. But folic acid is excluded from the result because it is a TS ligand. fdUMP has similar structure with UMP, a TS ligand, but folic acid which has lowest docking score is not similar with UMP. Conclusions: The 26 compounds, except folic acid, are more potent than 5-FU as TS inhibitors by docking study. Further study to delineate the effectivity of molecular docking is needed. Keywords: 5-Fluorouracil, herbal compound, molecular docking, thymidylate synthase